2021
DOI: 10.1186/s12931-021-01878-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental endothelial locus-1 as a potential biomarker for the incidence of acute exacerbation in patients with chronic obstructive pulmonary disease

Abstract: Background Despite the high disease burden of chronic obstructive pulmonary disease (COPD) and risk of acute COPD exacerbation, few COPD biomarkers are available. As developmental endothelial locus-1 (DEL-1) has been proposed to possess beneficial effects, including anti-inflammatory effects, we hypothesized that DEL-1 could be a blood biomarker for COPD. Objective To elucidate the role of plasma DEL-1 as a biomarker of COPD in terms of pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…In our previous study, the protective effect of Del-1 in response to CSE was demonstrated through increased emphysema in Del-1 KO mice [11]. Consistent with this, Del-1 levels were found to be lower in lung homogenates from patients with COPD than those from smokers without COPD.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In our previous study, the protective effect of Del-1 in response to CSE was demonstrated through increased emphysema in Del-1 KO mice [11]. Consistent with this, Del-1 levels were found to be lower in lung homogenates from patients with COPD than those from smokers without COPD.…”
Section: Discussionsupporting
confidence: 75%
“…Previously, we have shown that plasma levels of Del-1 are lower in patients with COPD and that this reduced Del-1 level predicts the subsequent risk of AE-COPD [11]. These findings suggest that extracellular soluble Del-1 plays a protective role against the development of both COPD and AE-COPD.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…EDIL3 (EGF-like repeat and discoidin I-like domain-containing protein 3) is an integrin ligand that promotes adhesion of endothelial cells and is involved in angiogenesis and vascular remodeling. Plasma levels of EDIL3 have been shown to be decreased in COPD patients and associated with increased risk of acute exacerbation [80]. CRLD2 (Cysteine-rich secretory protein LCCL domain-containing 2) [CRISPLD2] is a secreted protein that promotes matrix assembly and modulates airway branching and alveogenesis [81].…”
Section: Resultsmentioning
confidence: 99%